I think, but I wouldn't want to bet serious money on it, that solving for c last is the way to go. Equation 2 and equation 3 both have one as the numerical coefficient for c, so you could equate the rest of the equation with each other.
Step one
Isolate c on Equation 3
Add 4x to both sides.
2y + 4x = c
Step 2
Isolate c in equation two.
It is isolated. Equate the left hand sides of each equation
2y + 4x = (5/3)x + y Multiply by 3
Step 3
Solve for ax + by
6y + 12x = 5x + 3y Subtract 3y from both sides.
3y + 12x = 5x Subtract 5x from by sides.
3y + 7x = 0
Step 4
Use equation 1
3y + 7x = 0
y + x = 6 Multiply this equation by 3
3y + 7x = 0
3y + 3x = 18 Subtract
4x = - 18
x = - 4.5
x + y = 6
-4.5 + y = 6 Add 4.5 to both sides.
y = 10.5
So far we have
x = - 4.5
y = 10.5
Now we have to solve for c
In case I run out of time, c = 3
4x + 2y = c
4*(-4.5) + 2(10.5) = c
-18 + 21= c
c = 3 <<<<<< answer.
I cannot tidy this up. I'm being timed. The answers are correct however.